Antioxidant activities and stability of seed Kernel extracts from mango (Mangifera indica linn.) cultivated in Northern Thailand - Nakpanich N. (2017)
© 2017, Chiang Mai University. All rights reserved. Mango seeds are normally discarded as wastes, after processing of the mango pulp into different product, and accumulated more every year. Therefore, this study aimed to investigate the antioxidant activity of the mango seed kernel extracts (cultivar Keawmorakot and Mahachanok, both ripe and raw). The phytochemical constituents of the extracts were screened and phenolic compounds were observed in all extracts. Total phenolic contents of each extract were then determined using Folin-ciocalteu’s reagent, and the radicals scavenging activity of each extract was performed using 1,1-diphenyl-2-picrylhydrazyl (DPPH)-radical scavenging assay, and 2,2′-Azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS)-radical scavenging assay. Linoleic acid peroxidation inhibition assay was evaluated using ferric thiocyanate method. The ripe Mahachanok extract (MS) exhibited the highest antioxidant activity in DPPH, ABTS-radical scavenging assay and linoleic acid peroxidation inhibition assay, with IC50 value of 8.055 ± 0.274 μg/mL, 3.215 ± 0.091 μg/mL, and 0.233 ± 0.021 μg/mL, respectively. The chemical profile of the mango seed kernel extracts was investigated using HPLC and showed that the major constituent of each extract was gallic acid, which was likely to be the major active compound that possesses the antioxidant activity. Furthermore, the stability of each extract in various conditions was performed in four conditions, which demonstrated that the antioxidant activity and the amount of gallic acid in all extracts were not significantly changed after storing at room temperature with light, room temperature in the dark, 45°C, and 4°C for 3 months.